2021
DOI: 10.1038/s41467-021-21120-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the small ATP-independent chaperone Spy is substrate specific

Abstract: ATP-independent chaperones are usually considered to be holdases that rapidly bind to non-native states of substrate proteins and prevent their aggregation. These chaperones are thought to release their substrate proteins prior to their folding. Spy is an ATP-independent chaperone that acts as an aggregation inhibiting holdase but does so by allowing its substrate proteins to fold while they remain continuously chaperone bound, thus acting as a foldase as well. The attributes that allow such dual chaperoning b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…For understanding the process better, kinetic information is important. Recent studies focusing on the binding kinetics between the chaperone and client proteins [ 13 , 15 , 16 , 17 , 63 , 64 ] have revealed that the chaperone–client complex is dynamic and mediated by fast binding–release exchange [ 16 , 54 ]. Furthermore, the foldase and holdase activities of molecular chaperones are related to the binding kinetics between the chaperone and client protein and to the folding speed of the client protein [ 16 ].…”
Section: Kinetic Studies For Molecular Chaperones and Client Proteinsmentioning
confidence: 99%
“…For understanding the process better, kinetic information is important. Recent studies focusing on the binding kinetics between the chaperone and client proteins [ 13 , 15 , 16 , 17 , 63 , 64 ] have revealed that the chaperone–client complex is dynamic and mediated by fast binding–release exchange [ 16 , 54 ]. Furthermore, the foldase and holdase activities of molecular chaperones are related to the binding kinetics between the chaperone and client protein and to the folding speed of the client protein [ 16 ].…”
Section: Kinetic Studies For Molecular Chaperones and Client Proteinsmentioning
confidence: 99%
“…Similar growth retardation was observed in cells expressing Spy D26K , but not in cells expressing Spy D26E . It has been shown that the folding rate of clients bound to Spy is much slower compared to their spontaneous folding in solution 21 , 32 , 33 . Consistent with this, we observed a similar inhibitory effect of Spy on the folding rate of another client, α-LA, and noted that the variant Spy 29-138 retarded α-LA folding more severely than the Spy wild type (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to that, opp operon (oppABCDF) that encodes the components in a polyamine-induced oligopeptide ABC transport system is upregulated for the transport of hydrophilic substances to compensate for the hydrophobic pressure exerted by alcohols [137,138]. Genes responsible for response to heat shock and extracytoplasmic stress (cpx regulon) are upregulated, and periplasmic chaperone Spy is encoded to respond to protein misfolding activity [139][140][141][142]. Increased isobutanol tolerance of C. acetobutylicum is also conferred to overexpression of genes related to heat shock [139,143].…”
Section: Stress Response Systemmentioning
confidence: 99%